Social Networks and their Mathematical Modeling - Ortega Guerrero, Juan Carlos (2016)
The information and communication technologies (ICT) have come to change the potential of social networks. Their diversity, scope and characteristics are creating a great impact on society, and their mathematical analysis is important to understand that. This chapter describes the basic concepts of networks; we will see how complex networks and their main characteristics are generated, especially small-world networks and their use to model social networks will be analyzed. Finally, some limitations with these mathematical models in the representation of social reality are described.